Stratigraphy, sedimentology and petrology of the Cambrian rocks in the subsurface of Southern Alberta, Canada - Tawadros, Ezzat Edward (University of St Andrews, 2017)
The Cambrian section in the subsurface of southern Alberta has a maximum thickness of 1860'. It is composed of sandstones, shales, limestones, and dolomites. The grand cycles characteristic of the Cambrian Sections in the Foothills and Front Ranges can be traced to some distance in the subsurface. However, the section changes facies eastwards into clastics and the grand cycles become less defined. The present correlations indicate that the Waterfowl-Arctomys grand cycle extends to the subsurface but is restricted to the northwest corner of the study area. Two new stratigraphic units have been informally defined in this study: The Crow Indian Formation of fine clastics and restricted to the southeast corner of Alberta. It is equivalent to the Cathedral, Stephen and Eldon Formations. The second unit is the Sakwatamau Member of the Eldon Formation, a clastic and carbonate deltaic unit restricted to the northwest corner of the study area. The Cambrian sediments were deposited in a broad shallow shelf-lagoon bordered to the east by the Canadian Shield and to the west by a shoal (the Kicking Horse Rim). Facies and thickness of the Cambrian section were controlled by six paleogeographic elements: 1) The Peace River Arch, 2) the Sweet Grass Arch, 3) the West Alberta Ridge, 4) the Kicking Horse Rim, 5) a shoal area immediately south of the Peace River Arch, and 6) a shoal area immediately north of the Sweet Grass Arch. When circulation in the shelf-lagoon was restricted, carbonate deposition dominated, especially in the shoal areas, and when open marine conditions prevailed, deposition of quartzarenites and glauconitic sandstones took place. Nine lithofacies have been recognized; 1) Mottled dolomitic mudstones and wackestones; 2) Mudstones, wackestones, and packstones; 3) Grainstones; 4) Cryptalgalaminates, cryptalgalaminate breccia, and algal-laminated sediments; 5) Flat-pebble conglomerates; 6) Glauconitic sandstones; 7) Quartzarenites; 8) Hybrid sandstones or iron-formations, and 9) Coquinas. These facies reflect ...